Molecular Analyses and Resistance Evaluation to Bacterial Leaf Blight on Swampy Rice Genotypes - Ahmad Dadang; Siti Yuriah; Nonon Saribanon; Joko Prasetiyono; Dwinita Wikan Utami (Jurnal AgroBiogen, 2021)
Swampland is a prospective marginal land to be developed for rice cultivation. Rice plants that are adaptive to swampland usually have good tolerance to Fe. Previously, we obtained several rice lines tolerant to Fe toxicity in the field. This study aimed to analyze the swampy rice genotypes using STS molecular markers linked to bacterial leaf blight (BLB)-resistant genes and evaluate the resistance level of the genotypes against three BLB races under the greenhouse condition. This research was conducted in the Molecular Biology Laboratory and Greenhouse of the Indonesian Center for Agricultural Biotechnology andGenetic Resources Research and Development from January to May 2021. Eighteen swampy rice varieties/lines and two check varieties for Fe toxicity and BLB, respectively, were used in this research. The eight STS molecular markers linked to BLB resistance genes were used for genotyping analysis. The results showed that all rice plants tested contained xa5 allele gene, 19 genotypes had Xa4 allele gene, 17 genotypes had Xa7 allele gene, 9 genotypes had xa13 allele gene, 5 genotypes had xa13 allele gene, and 6 genotypes had Xa4 and Xa21 allele genes. Line B146E-4 was estimated to have 7 resistance alleles genes, meanwhile lines B14301E-KA-17-a, B14315E-KA-1, and B13-1-a have 6 resistance allele genes. The resistance evaluation of the genotypes against the three BLB races (races III, IV, and VIII) under the greenhouse condition showed that line B14315E-KA-1 was confirmed to be highly resistant to BLB disease. This line can be a promising candidate for swampy rice that is resistant toBLB disease.